The problem of cholecalciferol deficiency among patients with arterial hypertension - Bezborodov, A. S.; Sid, Ye. V.; Сідь, Євген Володимирович (My University, 2025)
Annotation: аrterial hypertension (AH) remains the leading modifiable risk factor of cardiovascular diseases, stroke, and chronic kidney disease. Its high prevalence and close connection with cardiovascular diseases and premature death determine the relevance of this problem for health care systems worldwide. Recently, vitamin D deficiency has acquired the status of a pandemic, affecting more than a billion people regardless of age and ethnic belonging. This has generated a central scientific hypothesis: whether this connection is causal, or the observed association is only an epiphenomenon reflecting other risk factors, such as obesity, sedentary lifestyle, and general health condition? During the recent time, there is a growing body of data indicating a significant connection between low vitamin D levels and various cardiovascular diseases and conditions.
Keywords: vitamin D; endothelium; hypertension; cardiovascular; renin